CRITICISM OF HELPING MECHANISM FOR CONFIRMED COVID-19 PATIENTS IN MAJALENGKA DISTRICT - Elya Kusuma Dewi (Faculty of Law, Khairun University, 2021)
This article was written with the aim of knowing and analyzing the policies of the Majalengka Regency Government in providing assistance to people who are self-isolating due to being exposed to or confirmed positive for Covid-19, besides that this paper will also try to describe about how the mechanism for providing assistance as well as analyzing weaknesses and solutions to these problems.This paper is a normative juridical writing made with two main approaches, namely the empirical approach and the case approach.The results of the study indicate that the policy of providing assistance for people who are self-isolating in Majalengka Regency is given by providing cash assistance worth Rp. 45.000,00 (forty five thousand rupiah) with details of 3 (three) meals/improvement of nutrition per day multiplied by Rp. 15,000.00 (fifteen thousand rupiah), wherein the amount is given for 10 days of self-isolation period. If it is calculated as a whole, then the total compensation given to residents/communities who do self-isolation is Rp. 45.000,00 X 10 days, which is Rp. 450,000.00 per one citizen identified as positive for Covid-19. However, the facts on the ground show that there are still many community members who do not and do not know about the program, this is due to the existence of a mechanism for providing assistance that focuses on managing the residents, not the government, so it is necessary to reconstruct/change the distribution mechanism which emphasizes the importance of government activities. in the distribution of assistance to the people of Majalengka Regency who were confirmed positive for Covid-19.